State inequality, socioeconomic position and subjective cognitive decline in the United States - Rachel L. Peterson; Scott C. Carvajal; Lisa C. McGuire; Mindy J. Fain; Melanie L. Bell (Elsevier, 2019)
Background: Social gradients in health have been observed for many health conditions and are suggested to operate through the effects of status anxiety. However, the gradient between education and Alzheimer's disease is presumed to operate through cognitive stimulation. We examined the possible role of status anxiety through testing for state-level income inequality and social gradients in markers of socioeconomic position (SEP) for Alzheimer's disease risk. Methods: Using data from the cross-sectional 2015 and 2016 Behavioral Risk Factor Surveillance System (BRFSS) and the U.S. Census Bureau's American Community Survey, we tested for the association between U.S. state-level income inequality and individual SEP on subjective cognitive decline (SCD) - a marker of dementia risk - using a generalized estimating equation and clustering by state. Results: State income inequality was not significantly associated with SCD in our multivariable model (OR 1.2; 95% CI: 0.9, 1.6; p=0.49). We observed a clear linear relationship between household income and SCD where those with an annual household income of 50k to 75k had 1.4 (95% CI: 1.3, 1.6) times the odds and those with household incomes of less than $10,000 had 4.7 (95% CI: 3.8, 5.7) times the odds of SCD compared to those with household income of more than $75,000. We also found that college graduates (ref.) and those who completed high school (OR: 1.1; 95% CI 1.04, 1.2) fared better than those with some college (OR: 1.3, 95% CI 1.2, 1.4) or less than a high school degree (OR: 1.5; 95% CI: 1.4, 1.7). Conclusions: Income inequality does not play a dominant role in SCD, though a social gradient in individual income for SCD suggests the relationship may operate in part via status anxiety. Keywords: Aging, Alzheimer's disease, Cognitive decline, Income inequality, Socioeconomic factors, BRFSS